Egyptian Journal of Medical Human Genetics - M. Shawky, Rabah; SpringerLink (Online service) (Berlin/Heidelberg : Springer Berlin Heidelberg : Imprint: Springer.)
Egyptian Journal of Medical Human Genetics (EJMHG) is an open access, peer-reviewed journal with a focus on reporting innovations within the field of human and medical genetics. The journal considers articles on all aspects of the genetic basis of human disease, with a particular emphasis on biochemical genetics, biological studies of enzymes and other protein deficiencies, as well as immunogenetics. Other topics of interest include investigations of the pathogenesis of inherited disorders and practical advances in the molecular diagnosis of human disease. Articles presenting clinical applications of genomics and next generation sequencing technologies are considered valuable contributions. Egyptian Journal of Medical Human Genetics welcomes submissions of editorials, research, reviews, case reports, correspondence, meta-analysis and commentaries.
Keywords: Medicine; Medicine/Public Health, general